Bản tổng hợp, giải trình, tiếp thu ý kiến góp ý đối với Dự án Luật Thủ đô (sửa đổi) (Tính đến ngày 28/8/2023) - Bộ Tư pháp (2023)
Toàn văn Bản tổng hợp, giải trình, tiếp thu ý kiến góp ý đối với Dự án Luật Thủ đô (sửa đổi) (Tính đến ngày 28/8/2023).